Desempenho de leitura e escrita de palavras isoladas e pseudopalavras de escolares do 3º ano - Prates, Ana Cristina Melo (2017)
Reading and writing learning, as well as students’ difficulties in this process, is a recurrent theme in Educational Speech-Language Pathology research and in other correlated areas. This research had the objective to describe and analyze Reading and writing performance of isolated words and pseudowords of 3º year students of Guaíba-RS municipal public educational system that had concluded PNAIC literacy cycle. We searched to describe and analyze reading and writing performance of isolated words and pseudowords of students, as well as preferential routes used by them. We selected 146 students from 15 schools, which were submitted to two reading and writing test batteries. Results were analyzed using descriptive statistics, multivariate analysis and correlation tests. Results indicated a great variability of evaluated students’ performance, both internally and between schools. Reading performance was higher, indicating a balance between both routes, especially in satisfactory assessment. Considering writing evaluation, results were below expected for 3d year, in literacy final phase. In these a predominance of phonological route was demonstrated, indicating a fail in systematization of Portuguese language teaching. Our results pointed to a necessity of school speech therapist to contribute to institutional diagnosis and for planning interventions on literacy process.